Some New Beesack–Wirtinger-Type Inequalities Pertaining to Different Kinds of Convex Functions - Artion Kashuri; Muhammad Samraiz; Gauhar Rahman; Zareen A. Khan (Mathematics, 2022)
In this paper, the authors established several new inequalities of the Beesack–Wirtinger type for different kinds of differentiable convex functions. Furthermore, we generalized our results for functions that are n-times differentiable convex. Finally, many interesting Ostrowski- and Chebyshev-type inequalities are given as well.